EKONOMI BIAYA TINGGI, INVESTASI DAN PERTUMBUHAN EKONOMI - Abukosim Abukosim; Taufiq Marwa (Department of Development Economics, Universitas Sriwijaya, 2009)
This paper attempts to uncover the link between high-cost economy, investment, and economic growth. The method used is the study of literature by using data published by the authorities. Revealed in this paper that in order to overcome the problem of high-cost economy, among them, needs to be done to minimize the illegal levies and corruption that exist, both within government agencies and non-governmental actors in the environment of investment location, the bureaucracy is too long need to be pruned, one only by imposing licensing under one roof in order to provide fast service, cheap and efficient, there must be certainty of the law in force in the region for investors to feel safe to invest (ex: land, security, etc.), need to review back and revise local regulations that would complicate the parties that want to invest (there is a tendency in the era of regional autonomy under the pretext of increasing revenue, levies appear that legalized. South Sumatra Province is rich in natural resources in dire need of investment funds to cultivate the potential of natural resources, so as to excavated and beneficial to economic growth and welfare of the people of South Sumatra. Because of the potential that exists in South Sumatra is closely related to the primary sector (agriculture and mining) are strongly associated with the land, the legal certainty regarding landÂ needs special attention.Keywords: High-Cost Economy, Investment, Economic Growth